The miR-15a/16-1 and miR-15b/16-2 clusters regulate early B cell development by limiting IL-7 receptor expression - Hutter, Katharina; Rülicke, Thomas; Szabo, Tamas G.; Andersen, Lill; Villunger, Andreas; Herzog, Sebastian (Frontiers in Immunology, 2022)
MicroRNAs are small non-coding RNAs that have emerged as posttranscriptional regulators involved in development and function of different types of immune cells, and aberrant miRNA expression has often been linked to cancer. One prominent miRNA family in the latter setting is the miR-15 family, consisting of the three clusters miR-15a/16-1, miR-15b/16-2 and miR-497/195, which is best known for its prominent tumor suppressive role in chronic lymphocytic leukemia (CLL). However, little is known about the physiological role of the miR-15 family. In this study, we provide a comprehensive in vivo analysis of the physiological functions of miR- 15a/16-1 and miR-15b/16-2, both of which are highly expressed in immune cells, in early B cell development. In particular, we report a previously unrecognized physiological function of the miR-15 family in restraining progenitor B cell expansion, as loss of both clusters induces an increase of the pro-B cell as well as pre-B compartments. Mechanistically, we find that the miR-15 family mediates its function through repression of at least two different types of target genes: First, we confirm that the miR-15 family suppresses several prominent cell cycle regulators such as Ccne1, Ccnd3 and Cdc25a also in vivo, thereby limiting the proliferation of progenitor B cells. Second, this is complemented by direct repression of the Il7r gene, which encodes the alpha chain of the IL-7 receptor (IL-7R), one of the most critical growth factor receptors for early B cell development. In consequence, deletion of the miR-15a/16-1 and miR-15b/16-2 clusters stabilizes Il7r transcripts, resulting in enhanced IL-7R surface expression. Consistently, our data show an increased activation of PI3K/AKT, a key signaling pathway downstream of the IL-7R, which likely drives the progenitor B cell expansion we describe here. Thus, by deregulating a target gene network of cell cycle and signaling mediators, loss of the miR-15 family establishes a pro-proliferative milieu that manifests in an enlarged progenitor B cell pool.